Factores de comportamiento de compra que influyen en el consumidor millennial del cantón Yacuambi, provincia de Zamora Chinchipe, al decidir adquirir alimentos (frutas y verduras). - Paqui Guaillas, Nancy Beatriz (2022)
This research focused on identifying the purchasing behavior factors that influence the millennial consumer in the Yacuambi canton, province of Zamora Chinchipe, when deciding to purchase food (fruits and vegetables). A mixed methodology of exploratory character was applied, with a simple transversal descriptive tool, because all the information was collected in a single time; the deductive and inductive method was also used. The information was collected through a 15-question survey conducted personally and online to a sample of 336 consumers of the millennial generation (people between 21 and 41 years old). The results showed that the most predominant factors in the purchase decision of this population group are economic circumstances, life cycle and lifestyle (personal factor), experience (psychological factor) and the opinion of the family (social factor), i.e., although their purchasing power is low, the need to consume healthy products leads them to purchase fruits and vegetables, although in small quantities. The consumption of these products is given by their own initiative in order to preserve their health, habits that have changed since the COVID-19 pandemic, as stated by 42.56%, the amount of purchase and consumption varies depending on the type of fruits and vegetables, their mode of consumption is distributed in the five daily meals in various preparations, where the main responsible for the purchase is the mother. Key words: Consumer behavior, purchase decision, fruits and vegetables, millennial generation.